Surgical treatment of hallux valgus using a modified Reverdin-Isham technique - Lara, Luiz; Torres Filho, Lúcio; Cervone, Gabriel; Grajales, Juan; Bordignon, Glaucia; Lancia, Lara Furtado; Santos, Diego (Journal of the Foot & Ankle, 2021)
Objective: To evaluate the postoperative results of patients who underwent surgical treatment of hallux valgus with a modified Reverdin-Isham (RI) technique and to compare the achieved correction with that reported by studies using the original technique. Methods: This is a retrospective study with patients with mild to moderate hallux valgus who underwent surgery from June 2010 to July 2019. All patients were operated using the modified RI technique. Data were collected through the American Orthopaedic Foot and Ankle Society (AOFAS) questionnaire, in addition to pre and postoperative radiographic studies of the intermetatarsal angle (IMA), the hallux valgus angle (HVA), and the distal metatarsal articular angle (DMAA). Results: The mean postoperative follow-up was 30.1 months, and the mean age of patients was 56.4 years. The median AOFAS score in the postoperative period was increased by 56 points. The mean HVA was reduced in 16.5°, the mean IMA was reduced in 4.3°, and the mean DMAA was reduced in 10°. There were no cases of displacement or deviation of the first metatarsal head during the postoperative follow-up. Conclusion: The modified RI technique provided considerable stability to the osteotomy, in addition to a significant correction of the measured angles and an improvement in AOFAS scores, demonstrating itself as an effective technique for correcting mild to moderate hallux valgus. Level of Evidence IV, Therapeutic Studies, Case Series.